Bi0.5K0.5TiO3–CaTiO3 ceramics: Appearance of the pseudocubic structure and ferroelectric‐relaxor transition characters. Issue 6 (13th December 2018) - Wei, Yongxing; Zhang, Ning; Jin, Changqing; Zhu, Weitong; Zeng, Yiming; Xu, Gang; Gao, Ling; Jian, Zengyun
Abstract: In this study, solid solution ceramics of (1− x )Bi0.5 K0.5 TiO3 – x CaTiO3 (BKT‐CT, x = 0, 0.12, 0.15, 0.18, 0.21, and 0.25) were prepared. A phase transition from the tetragonal symmetry to the pseudocubic symmetry is discovered near x = 0.25. The reasons for the appearance of the pseudocubic phase were discussed. The compositions of x ≤ 0.21 show the ferroelectric ordering at room temperature. The remnant polarization ( P r ) is 22.4 μC/cm 2 for the x = 0.15 composition. The temperature dependence of the relative permittivity suggests two dielectric anomalies for x ≤ 0.18. The dielectric anomaly in the low‐temperature range is related to a spontaneous transition between the ferroelectric and relaxor states. The temperature ( T F‐R ) for the transition decreases with the CT addition, falling from 211°C for x = 0.12‐134°C for x = 0.18. Only one relaxor‐like dielectric anomaly was observed for x ≥ 0.21. The thin double ferroelectric hysteresis loops have been observed during the ferroelectric‐relaxor transition process for x ≥ 0.21. The maximum electrostrain ( S m ) reaches 0.155% at 100°C for x = 0.21. The low‐temperature Raman measurement suggests the intrinsic tetragonal distortions for x = 0.25. Abstract : Dielectric behavior, polarization and strain responses during the ferroelectric‐relaxor transition process of 0.79BKT‐0.21CT.